2019
DOI: 10.3122/jabfm.2019.04.180326
|View full text |Cite
|
Sign up to set email alerts
|

Physician and Family Discussions about Driving Safety: Findings from the LongROAD Study

Abstract: on behalf of the LongROAD Research Team Background: Older adult drivers may experience decreases in driving safety with age or health status change. Discussing driving safety may help them plan for driving restriction and eventual cessation. Here, we sought to examine conversations between older adults and their family members and physicians. Methods: In this multi-site cross-sectional analysis of baseline data from the AAA Longitudinal Research on Aging Drivers (LongROAD) cohort study, we measured the prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 21 publications
1
6
0
1
Order By: Relevance
“…Other studies have also found that physicians rarely discussed driving or TA risks with their older patients [ 37 ]. For example, a 2019 study by Betz et al noted that only 29% of older people included in the LongROAD study cohort had had conversations with their doctor about medication use, driving, and related topics [ 26 ]. However, a study in Switzerland by Sebo et al found that 96% of all FD often or always asked their older patients who drove about the list of their current medications, 88% inquired about their use of antidiabetic drugs, and 65.5% asked patients about their use of psychotropic drugs [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have also found that physicians rarely discussed driving or TA risks with their older patients [ 37 ]. For example, a 2019 study by Betz et al noted that only 29% of older people included in the LongROAD study cohort had had conversations with their doctor about medication use, driving, and related topics [ 26 ]. However, a study in Switzerland by Sebo et al found that 96% of all FD often or always asked their older patients who drove about the list of their current medications, 88% inquired about their use of antidiabetic drugs, and 65.5% asked patients about their use of psychotropic drugs [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies of FD or of older patients have focused on factors related with medication use and TA. The relatively few studies published to date have centred on how frequently FD ask their older patients about the use of medications that might affect their driving, and on whether FD offer these patients advice regarding the risk of driving while using these drugs [ 22 – 26 ]. In Spain, unfortunately, there appear to be no studies of the association between medications and the risk of TA among older drivers.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this, healthcare professionals must fully understand the social environment of the patient and their family and ensure an environment amenable to advice-seeking by patients. Research into communication between healthcare professionals and elderly drivers has identified that persuasive messaging includes elements of trust, emotion, and context [33] and that it takes time for patients to relinquish driving [34]. A study on safe driving among older drivers, families, and physicians also revealed that very few older drivers discussed safety practices with their families, which was consistent with participants' living environment [35].…”
Section: Antihistaminesmentioning
confidence: 93%
“…This study was based on the Ͼ10% of adults who responded positively to 1 question on worry about paying rent or mortgage over the past year. However, Betz et al 11 report that driving safety does not seem to be a priority for aging adults, their physicians, or their families.…”
Section: Patient Priorities For Carementioning
confidence: 99%